The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1091/mbc.e08-08-0885
|View full text |Cite
|
Sign up to set email alerts
|

Aurora B Kinase Regulates the Postmitotic Endoreduplication Checkpoint via Phosphorylation of the Retinoblastoma Protein at Serine 780

Abstract: The phenotypic change characteristic of Aurora B inhibition is the induction of polyploidy. Utilizing specific siRNA duplexes and a selective small molecule inhibitor (AZD1152) to inhibit Aurora B activity in tumor cells, we sought to elucidate the mechanism by which Aurora B inhibition results in polyploidy. Cells treated with AZD1152 progressed through mitosis with misaligned chromosomes and exited without cytokinesis and subsequently underwent endoreduplication of DNA despite activation of a p53-dependent p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 40 publications
8
89
0
1
Order By: Relevance
“…One of the key effector proteins regulated by Aurora B kinase is the RB1 protein (29). However, the RB1 protein expression was not related to the in vivo response of the AS703569 inhibitor in this study, which is in line with previous reports showing that RB1 status alone does not correlate with sensitivity to Aurora kinase inhibitors in vivo (21,30).…”
Section: Discussionsupporting
confidence: 87%
“…One of the key effector proteins regulated by Aurora B kinase is the RB1 protein (29). However, the RB1 protein expression was not related to the in vivo response of the AS703569 inhibitor in this study, which is in line with previous reports showing that RB1 status alone does not correlate with sensitivity to Aurora kinase inhibitors in vivo (21,30).…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, the checkpoint activation causes a G 1 arrest only after MLN8054, which is required to induce apoptosis, but not after ZM447439 treatment, whose efficacy even requires a severe polyploidization. Interestingly, the latter might be related to the most recently discovered phosphorylation of the Rb tumor suppressor protein by Aurora-B, which might contribute to the cell cycle arrest in the postmitotic G 1 phase on unscheduled exit from mitosis (39). In agreement with this, we found that endoreduplication, and thus apoptosis, after Aurora-B inhibition by ZM447439 is not dependent on p53.…”
Section: Discussionsupporting
confidence: 86%
“…This p53 dependency for Aurora A inhibition is very distinct from that of Aurora B inhibition, in which all cell types resulted in polyploidy independent of the p53 status. 18 However, in order to rule out any off-target effect on Aurora B, we used Aurora B kinase with histone H3 in an in vitro kinase assay, and no inhibition was observed, with MK8745 further confirming MK8745 as an inhibitor of Aurora A and not Aurora B. p53 (S315), PLK (S137), Aurora A (T288), known substrates of Aurora A 21 also used to further validate target inhibition in the in vitro assay.…”
Section: Methodsmentioning
confidence: 99%
“…17 However, we have shown previously that AZD 1152HQPA, a specific inhibitor of Aurora B kinase, induces polyploidy independent of p53 status of the cell line. 15,18 Even though many small-molecule inhibitors are undergoing clinical trials, it is still unclear whether polyploidy can be taken as a mechanism of cell death. It is also not certain whether polyploid cells eventually die or become aneuploid.…”
Section: The Induction Of Polyploidy or Apoptosis By The Aurora A Kinmentioning
confidence: 99%
See 1 more Smart Citation